PENGARUH KEJELASAN SASARAN ANGGARAN, AKUNTABILITAS PUBLIK, DAN SISTEM PELAPORAN TERHADAP KINERJA MANAJERIAL (Studi Empiris Pada SKPD Kabupaten Rokan Hulu) - Efrizar, Rona; ', Hardi; Wiguna, Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of the Budget Targets Clarity Managerial Performance, Public Accountability on Managerial Performance and Reporting System on Managerial Performance. This study was a quantitative research. The sample is determined by using purposive sampling and sampling for each SKPD using the proportional method. The sample in this study was 81. Data were analyzed using multiple regression with SPSS version 20. The results showed that the Budget Targets Clarity positive effect on Managerial Performance, Public Accountability positive effect on Managerial Performance and Reporting System positive effect on Managerial Performance. The results of this study indicate that the first, related to the Budget Goal Clarity Managerial Performance with t count 3,177> 1,991 and 0,002 significant <0.05. Second, the Public Accountability for Managerial Performance with t count 3.585> 1.991 and 0.001 significant <0.05. Third, the Reporting System for Managerial Performance with t count 2,547> 1,991 and 0,013 significant <0.05. Determination coefficient (Adj-R2) This means that 56.8%. And then 43.2% had an impact by other variables.Keywords : managerial performance, clarity of budget objective, public accountability, and systems reporting